GROŽIO PATRAUKLUMAS. - Jonkus, Dalius (Problems / Problemos, 2015)
This paper analyses how Mickūnas's philosophy reveals the relationship between aesthetics and Eros. The purpose of this analysis is to show that aesthetics and Eros do not require representation, but presentation, and why these two aspects are related to the direct expression of world experience. The phenomenological analysis of aesthetics and Eros reveals the beauty of the world and its erotic appeal. Mickūnas argues that the aesthetic-erotic attitude is openness to the world's moods, rhythms and styles of being. On the other hand, he denies that the aesthetic and erotic experience is intentional, since the former is understood as a purposeful orientation to objects and an aim to identify the meaning of the object. In this paper I present arguments why Mickūnas's attempt to deny the intentionality of erotic and aesthetic experience is based on the narrow, rather than broad, concept of intentionality.